2021
DOI: 10.1111/bpa.12946
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific preservation of Purkinje cell morphology and motor behavior in the ATXN1[82Q] mouse model of spinocerebellar ataxia 1

Abstract: Purkinje cells are the primary processing units of the cerebellar cortex and display molecular heterogeneity that aligns with differences in physiological properties, projection patterns, and susceptibility to disease. In particular, multiple mouse models that feature Purkinje cell degeneration are characterized by incomplete and patterned Purkinje cell degeneration, suggestive of relative sparing of Purkinje cell subpopulations, such as those expressing Aldolase C/ zebrinII (AldoC) or residing in the vestibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 152 publications
(164 reference statements)
1
18
0
Order By: Relevance
“…Indeed, there exist molecules that are expressed in subsets of Purkinje cells in patterns that are more reminiscent of the patterning of degeneration we observe, such as PLCβ4 (Sarna et al, 2006), and it is likely that heterogeneity exists even within the zebrin bands that we describe. The predominantly zebrin-negative anterior-vermis degeneration observed here is reminiscent of several other forms of ataxia that show similar patterns of degeneration (Sarna and Hawkes, 2003), including SCA1 (White et al, 2021). It is possible that diseases that share similar patterns of cell degeneration may share common pathophysiological pathways (Niewiadomska-Cimicka et al, 2021), which suggests that common treatment strategies may be pursued for these disparate diseases.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Indeed, there exist molecules that are expressed in subsets of Purkinje cells in patterns that are more reminiscent of the patterning of degeneration we observe, such as PLCβ4 (Sarna et al, 2006), and it is likely that heterogeneity exists even within the zebrin bands that we describe. The predominantly zebrin-negative anterior-vermis degeneration observed here is reminiscent of several other forms of ataxia that show similar patterns of degeneration (Sarna and Hawkes, 2003), including SCA1 (White et al, 2021). It is possible that diseases that share similar patterns of cell degeneration may share common pathophysiological pathways (Niewiadomska-Cimicka et al, 2021), which suggests that common treatment strategies may be pursued for these disparate diseases.…”
Section: Discussionmentioning
confidence: 61%
“…The anterior-posterior differences in Purkinje cell firing properties have been associated with the expression profile of zebrin (Larouche and Hawkes, 2006): zebrin-positive cells are enriched in posterior lobules and fire at a lower frequency than zebrin-negative cells, which are enriched in anterior lobules (Xiao et al, 2014;Zhou et al, 2014). Since abnormal zebrin expression has been observed in rodent models of other forms of ataxia (Sawada et al, 2009;Sarna and Hawkes, 2011;Bailey et al, 2014;White et al, 2021), the changes in anterior-lobule firing that we previously reported (Ady et al, 2018) may likewise arise from abnormal expression of zebrin in the cerebellum in Sacs −/− mice. Conversely, intact neurotransmission from Purkinje cells to their downstream targets is required for proper zone formation in the cerebellum (White et al, 2014), and given that we have previously shown that Purkinje cells in Sacs −/− mice both fire at reduced frequencies and have deficits in their innervation of the CN (Ady et al, 2018), we wondered whether changes in Purkinje cell properties could themselves lead to disrupted zebrin patterning.…”
Section: Patterning Of Purkinje Cell Death In Autosomal-recessive Spastic Ataxia Of Charlevoix-saguenay Mouse Modelmentioning
confidence: 99%
“…The neuropathology is apparent from 5 to 6 wk and characterized by PC atrophy, disorganization of the PC monolayer with ectopic PCs, and reduction of calbindin (CaBP) expression. One feature of the Atxn1[82Q]/+ mouse model, also identified in the human pathology, is that the neurodegenerative process unfolds more rapidly in the anterior region, leaving the flocculonodular region spared ( 46 , 50 ) ( Fig. 1 D and E ).…”
Section: Resultsmentioning
confidence: 97%
“…As the region primarily affected by the pathology, the anterior cerebellum, exhibits higher S1P levels compared with the region preserved from the neuropathology (flocculonodular cerebellum), our working hypothesis was that in Atxn1[82Q]/+ mice, the increase of S1P has a proapoptotic effect. Indeed, we found that deletion of Sphk1 in Atxn1[82Q]/+ mutant mice improves the survival of PC, as observed with CaBP expression, PCs atrophy, and microglia activation, used as a readout for the spatiotemporal pattern of cerebellar neurodegeneration ( 50 , 56 ). In Allende et al ( 54 ), the authors found that in Sphk1 −/− mice, the kinase activity and S1P synthesis in brain homogenate were maintained at normal physiological levels and suggested that this was due to compensatory activity of Sphk2, a redundancy that explains why we did not observe a change in S1P levels in the Sphk1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation